High Familial Correlation in Methylphenidate Response and Side Effect Profile. Issue 2 (January 2019) - Gazer-Snitovsky, Michal; Brand-Gothelf, Ayelet; Dubnov-Raz, Gal; Weizman, Abraham; Gothelf, Doron
Objective: To examine whether a familial tendency exists in clinical response to methylphenidate.Method: Nineteen pairs of siblings or parent–child stimulant-naive individuals with ADHD were prescribed methylphenidate–immediate release, and were comprehensively evaluated at baseline, Week 2, and Week 4, using the ADHD Rating Scale IV, Clinical Global Impression Scale, and the Barkley Side Effects Rating Scale.Results: We found significant intraclass correlations in family member response to methylphenidate–immediate release and side effect profile, including emotional symptoms and loss of appetite and weight.Conclusion: Family history of response to methylphenidate should be taken into account when treating ADHD.